Porosity Quantification of Additive Manufactured Ti6Al4V and CoCrW Alloys Produced by L-PBF - R. Bidulský; P. Petroušek; J. Bidulská; R. Hudák; J. Živčák; M. Actis Grande (Archives of Metallurgy and Materials, 2022)
The main aim of the present paper is to evaluate the porosity and mechanical properties of Ti6Al4V and CoCrW alloys produced by Laser Powder Bed Fusion (L-PBF) as an additive manufacturing (AM) technology. Ti6Al4V and CoCrW alloys are attractive for medical application. The complex examination of porosity for these alloys needs the quantification of morphological and dimensional characteristics. Quantification of porosity was realized on non-etched samples. Quantitative image analysis was used to describe the dimensional and morphological porosity characteristics. The pores were evaluated by Image pro plus software. The results show the significant inhomogeneity of the morphology and distribution, as well as the pore size in the investigated materials and underline the importance of pore structure for the controlling mechanism of the mechanical response.